2002
DOI: 10.1128/jvi.76.24.12845-12854.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mamu-A*01 Allele-Mediated Attenuation of Disease Progression in Simian-Human Immunodeficiency Virus Infection

Abstract: Expression of several major histocompatibility complex (MHC) class I alleles is associated with a protective effect against disease progression in both human immunodeficiency virus type 1 and simian immunodeficiency virus infection. To understand the mechanism underlying this effect, we investigated the expression of the MHC class I allele Mamu-A*01 in simian-human immunodeficiency virus (SHIV) infection, one of the major models for evaluation of AIDS vaccine candidates. We found that disease progression was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 38 publications
8
81
3
Order By: Relevance
“…These investigations revealed a new association of Mauritian MHC haplotype and susceptibility/resistance to SHIV 89.6P infection. The association of particular MHC alleles with resistance of rhesus macaques to SIV and SHIV infection is well established [38][39][40][41][42][43]. Our results here extend the phenomenon to cynomolgus macaques of Mauritian origin.…”
Section: Introductionsupporting
confidence: 81%
“…These investigations revealed a new association of Mauritian MHC haplotype and susceptibility/resistance to SHIV 89.6P infection. The association of particular MHC alleles with resistance of rhesus macaques to SIV and SHIV infection is well established [38][39][40][41][42][43]. Our results here extend the phenomenon to cynomolgus macaques of Mauritian origin.…”
Section: Introductionsupporting
confidence: 81%
“…Recently published studies have suggested that Mamu A‫10ء‬ ϩ macaques fare better after SIV and recombinant SIV-HIV (SHIV) infections than Mamu A‫10ء‬ Ϫ animals do (79,115). Because each of our studies contained Mamu A‫10ء‬ ϩ animals, we examined the potential influence of Mamu A‫10ء‬ on our results.…”
Section: Fig 2 Antigen-specific T Cells In Immunized and Challenge mentioning
confidence: 99%
“…The increase in viral load indicated already that IL-15 treatment during acute infection may increase the normally slow progression of SIV infection in Mamu-A*01 ϩ rhesus macaques (45,46). We therefore followed the animals up to week 30.…”
Section: Il-15 Accelerated Disease Progression and Induced Meningoencmentioning
confidence: 99%